2013
DOI: 10.1186/1471-2334-13-13
|View full text |Cite
|
Sign up to set email alerts
|

Expression of M. tuberculosis-induced suppressor of cytokine signaling (SOCS) 1, SOCS3, FoxP3 and secretion of IL-6 associates with differing clinical severity of tuberculosis

Abstract: BackgroundAppropriate immune activation of T cells and macrophages is central for the control of Mycobacterium tuberculosis infections. IFN-γ stimulated responses are lowered in tuberculosis (TB), while expression of Suppressor of Cytokine Signaling (SOCS) molecules – 1 and 3 and CD4+CD25+FoxP3+T regulatory cells is increased. Here we investigated the association of these molecules in regard to clinical severity of TB.MethodsPeripheral blood mononuclear cells (PBMCs) were isolated from patients with pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 39 publications
6
45
2
Order By: Relevance
“…Signal downregulation through SOCS members has been demonstrated to be important in the balance of cytokines that determines the onset of Th1 and Th2-mediated immune responses. In particular, for cytokine-induced SOCS1 and SOCS3, a role in the regulation of T cell differentiation has been discussed (12)(13)(14).…”
Section: Cd4mentioning
confidence: 99%
“…Signal downregulation through SOCS members has been demonstrated to be important in the balance of cytokines that determines the onset of Th1 and Th2-mediated immune responses. In particular, for cytokine-induced SOCS1 and SOCS3, a role in the regulation of T cell differentiation has been discussed (12)(13)(14).…”
Section: Cd4mentioning
confidence: 99%
“…Moreover, Ifnar1 2/2 mouse macrophages express lower levels of Socs1 during mycobacterial infection, and IFN-g-activated Socs1 2/2 macrophages have lower intracellular bacteria as a result of the increased IFN-g signaling (91). These experimental findings, together with the clinical observation that increased SOCS protein expression correlates with increased disease severity (92,93), hint that a detrimental role for type I IFNs in M. tuberculosis infection is to antagonize host-protective functions of IFN-g. TB is not the only mycobacterial disease associated with type I IFN induction. Self-healing tuberculoid leprosy is traditionally associated with the development of a Th1 response, whereas disseminated lepromatous leprosy is characterized by a Th2 response.…”
Section: Mycobacteriamentioning
confidence: 91%
“…NK cells were produced IFN-γ as a triggers the activation of macrophages and increasing destruction of intracellular bacteria such as MTB [4]. Cytokine IFN-γ stimulated and activated macrophages to produce a substance that eliminates bacteria, including oxidase enzyme in phagocytes, such as reactive oxygen intermediates (ROI), enzyme inducible nitric oxide synthase, and enzyme lysozyme [4][5][6][7][8].…”
Section: Stimulation Of Antigen Mtb Will Response T-cells T-cell Cd4mentioning
confidence: 99%
“…Tregs are a subpopulation of CD4 + T-cells, expressing and secreting IL-10 and TGF-β, cytokine IL-10 as a barrier and decreasing Th 1 cell response in patients with TB infection. Tregs cells are a major source of cytokines IL-10, which serves to suppressed the function of APC and macrophages activation [4,5]. Infections TB were performed in mice showed that macrophages with excessive production of IL-10 causes of decreased production of ROI and RNI and reduced the function macrophages [11].…”
Section: Stimulation Of Antigen Mtb Will Response T-cells T-cell Cd4mentioning
confidence: 99%
See 1 more Smart Citation